Changing patterns in medication prescription for gestational diabetes during a time of guideline change in the USA: a cross‐sectional study. (8th November 2021) - Venkatesh, KK; Chiang, CW; Castillo, WC; Battarbee, AN; Donneyong, M; Harper, LM; Costantine, M; Saade, G; Werner, EF; Boggess, KA; Landon, MB
Abstract : Objective: To define patterns of prescription and factors associated with choice of pharmacotherapy for gestational diabetes mellitus (GDM), namely metformin, glyburide and insulin, during a period of evolving professional guidelines. Desing: Cross‐sectional study. Setting: US commercial insurance beneficiaries from Market‐Scan (late 2015 to 2018). Study design: We included women with GDM, singleton gestations, 15–51 years of age on pharmacotherapy. The exposure was pharmacy claims for metformin, glyburide and insulin. Main outcomes: Pharmacotherapy for GDM with either oral agent, metformin or glyburide, compared with insulin as the reference, and secondarily, consequent treatment modification (addition and/or change) to metformin, glyburide or insulin. Results: Among 37 762 women with GDM, we analysed data from 10 407 (28%) with pharmacotherapy, 21% with metformin ( n = 2147), 48% with glyburide ( n = 4984) and 31% with insulin ( n = 3276). From late 2015 to 2018, metformin use increased from 17 to 29%, as did insulin use from 26 to 44%, whereas glyburide use decreased from 58 to 27%. By 2018, insulin was the most common pharmacotherapy for GDM; metformin was more likely to be prescribed by 9% compared with late 2015/16, but glyburide was less likely by 45%. Treatment modification occurred in 20% of women prescribed metformin compared with 2% with insulin and 8% with glyburide. Conclusions: Insulin followed by metformin has replaced glyburide as the most common pharmacotherapy for GDM among a privately insured US population during a time of evolving professional guidelines. Further evaluation of the relative effectiveness and safety of metformin compared with insulin is needed. Tweetable abstract: Insulin followed by metformin has replaced glyburide as the most common pharmacotherapy for gestational diabetes mellitus in the USA. Tweetable abstract: Insulin followed by metformin has replaced glyburide as the most common pharmacotherapy for gestational diabetes mellitus in the USA. Linked article This article is commented on by AB Caughey, p. 484 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.16961 .